Gunkel’s Deconstruction: Between the Fetish and the Need for a Dialectical Renewal - Chankowski, Stanisław (Studia Philosophiae Christianae, 2022)
The purpose of the essay is to critically analyze the influence of J. Derrida’s deconstruction on David J. Gunkel’s book Deconstruction (MIT Press 2021). Gunkel’s handbook is aimed at making deconstruction a tool of critical thinking accessible to non-professionals. It turns out that accomplishing this task comes at the expense of precisely the critical potential of deconstruction itself. Gunkel is well aware that his arguments are sometimes superficial and overlook deeper problems that should be addressed. Such a failure takes the form of a fetishistic denial, which in psychoanalysis is summarized by the formula “I know well, but all the same.” In turn, deconstruction itself, insofar as it is separated from Kant’s transcendental philosophy and Hegel’s dialectics, becomes an academic ideology. Restoring its proper subversive potential can only be done by returning to a philosophy of reflection, in which the thinker himself must ultimately consider his own position as an author and bring it under criticism. This is the path that Gunkel avoids, because he could then no longer be the author of a handbook on deconstruction, rather than someone who practices deconstruction. ————————– Received: 4/11/2022. Reviewed: 13/12/2022. Accepted: 20/12/2022.